A systematic review on AI-enhanced pedagogies in higher education in the Global South - Khoza, Nomfundo Gladys; van der Walt, Freda (Frontiers in Education, 2025)
Artificial intelligence is gaining traction in higher education for its ability to simulate human intelligence and support learning processes. This systematic review investigates how artificial intelligence-enhanced teaching approaches are being applied in higher education institutions across the Global South. The study draws on peer-reviewed literature identified through a structured search of JSTOR and Web of Science databases, using clearly defined inclusion and exclusion criteria. The findings reveal that most applications focus on improving technical efficiency and administrative functions, while pedagogical integration remains limited. Key barriers include inadequate infrastructure, unequal access to digital tools, limited faculty preparedness, and ethical considerations. However, the review also highlights opportunities for locally adapted solutions and collaborative innovation. The study concludes with recommendations to guide policy and practice and outlines a future research agenda aimed at promoting equitable and context-sensitive use of artificial intelligence in higher education within the Global South.